Xerostomia after Radiotherapy for Oral and Oropharyngeal Cancer: Increasing Salivary Flow with Tasteless Sugar-free Chewing Gum - Kaae, Julie Killerup; Stenfeldt, Lone; Eriksen, Jesper Grau (Frontiers in Oncology, 2016)
Introduction: Radiation-induced xerostomia is a frequent late side effect after treatment for oral and oropharyngeal cancers. This may induce swallowing difficulties, compromised oral well-being, reduced nutrition intake, or speech deficiencies. Consequently, quality of life is often impaired for these patients. Objectives: The purpose was to investigate the possibility to mechanically stimulate residual saliva function by using tasteless and sugar free chewing gum. It was hypothesized that tasteless and sugar free chewing gum could immediately increase salivary flow and potentially improve oral well-being when used on a regular basis. Methods: From October to December 2014, 31 consecutive patients treated with primary radiotherapy and concomitant cisplatin (in locally advanced cases) for oral or oropharyngeal cancer consented to participate. All patients had finalized radiotherapy 2-8 months prior to participation and suffered from xerostomia. Samples of unstimulated and chewing gum stimulated saliva were obtained at the entry into the study (Visit 1). For two weeks, patients used chewing gum on a regular basis where upon saliva measurements were repeated to verify the changes (Visit 2). An abbreviated EORTC H&N35 questionnaire was completed for both visits. A small control group consisting of young and healthy individuals also tested the chewing gum. Results: 20 patients completed the study and an increase in saliva flow was observed for 14 patients. Before and after intervention with chewing gum, an increase in mean saliva output was seen between unstimulated and stimulated saliva for both Visit 1 and 2 (p=0.008 and p=0.05 respectively). No change in saliva output was seen in the control group. Conclusions: The chewing gum was able to stimulated saliva output which was seen at the beginning and at the end of the intervention. No improvement in baseline saliva was seen. Relevant changes in subjective measures of xerostomia were seen after two weeks of chewing gum.